Unexpected small molecules as novel SIRT2 suicide inhibitors. Issue 6 (15th March 2020) - Chen, Xiaoxue; Zou, Yefang; Wang, Jie; Cao, Zhuoxian; Liu, Jingzi; Li, Yan; Zhao, Yonglong; He, Bin
Graphical abstract: Abstract: A series of sirtuin inhibitor candidates were assembled based on an intermediate ester (1a ) our accidently discovered. After screening and evaluation, several SIRT2 selective inhibitors were identified, which can inhibit all the deacetylation, defatty-acylation and debenzoylation of SIRT2. Among these inhibitors, compound 1e was the best SIRT2 selective inhibitors. The primary study on the inhibitory mechanism indicated that compound 1e may be a suicide inhibitor acting as an irreversible way. Given almost all reported sirtuin inhibitors are non-covalent, sirtuin covalent inhibitors are still need to be developed. These findings will facilitate for further development of SIRT2 selective and suicide inhibitors.